Amplus Solar : the sky is the limit - Medicherla, Kiran; Agarawal, Shrey; Jamar, Arushi; Garg, Amit (London : Indian Institute of Management, Ahmedabad, 2018)
The use of solar energy is on the rise both internationally and in India. The Indian government target of 100 GW solar capacity by 2022 from the present 12 GW is providing a major push for growth in Indian solar energy industry. However, technological development and market competitiveness are pushing down the prices of solar power. The CEO of Amplus Solar, Sanjeev Aggarwal, has identified three options to combat these challenges: market expansion, to include customers with low creditworthiness, expanding to foreign geographies, diversification into providing energy efficiency and other services and entry into other markets such as REC and carbon trading. The student is invited to consider and justify, which of the three options they would choose to ensure the continued growth of Amplus Solar.
Originally Published InMedicherla, K., Agarawal, S., Jamar, A., & Garg, A. (2018). Amplus Solar – The Sky Is the Limit. PSG0127. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Aggarwal, Sanjeev; Amplus Solar; Solar energy industries -- India -- Case studies; Renewable energy sources -- India -- Case studies; Foreign trade promotion -- India -- Case studies; Competition -- India -- Case studies